Mapping livestock and poverty: A tool for targeting research and development - Thornton, Philip K.; Kristjanson, Patricia M.; Kruska, Russell L.; Reid, Robin S. (Cambridge University Press, 2004)
Detailed geographical profiles of poverty and inequality can be extremely valuable to governments, non-governmental organizations, and multilateral institutions that aim to strengthen the impact of their spending on poverty. Some developing countries use information on the geographical distribution of welfare indicators to guide the allocation of resources among local agencies or government as a first step in reaching the poor. Poverty maps can also be important tools for researchers.